Optimizing Explicit Model-Following Trajectory Control Laws for a Vectored Thrust Configuration - Comer, Anthony M.; Chakraborty, Imon (Journal of the American Helicopter Society, 2025)
The complex vertical takeoff and landing configurations currently under development necessitate flight control system design that enables substantial reductions of pilot workload through simplified vehicle operations. This paper shows optimization and simulation of such a flight control system architecture for a subscale vectored thrust aircraft configuration. A full-envelope trajectory control system for longitudinal dynamics was coupled with explicit model-following inner-loop controllers and a scheduled control allocation logic. Control system parameters were determined using a genetic algorithm optimization scheme subject to dynamic stability, robustness, and control responsiveness constraints. Flight simulation results for a series of representative maneuvers including departure and arrival transitions and forward flight maneuvers are presented to demonstrate the effectiveness of the proposed flight control system architecture.